Heaven Has No Favorites - Erich Maria Remarque (New York Random House Trade Paperbacks, 2014)
From one of the twentieth century's master novelists, the author of the classic All Quiet on the Western Front, comes Heaven Has No Favorites, a bittersweet story of unconventional love that sweeps across Europe. Lillian is charming, beautiful . . . and slowly dying of consumption. But she doesn't wish to end her days in a hospital in the Alps. She wants to see Paris again, then Venice-to live frivolously for as long as possible. She might die on the road, she might not, but before she goes, she wants a chance at life. Clerfayt, a race-car driver, tempts fate every time he's behind the wheel. A man with no illusions about chance, he is powerfully drawn to a woman who can look death in the eye and laugh. Together, he and Lillian make an unusual pair, living only for the moment, without regard for the future. It's a perfect arrangement-until one of them begins to fall in love.
Keywords: Classics; Fiction; Historical fiction